The meaning of race in psychology and how to change it: a methodological perspective - Helms, Janet E; Jernigan, Maryam; Mascher, Jackquelyn (The American psychologist, 2005)
The primary purpose of this article was to offer a methodological critique in support of arguments that racial categories should be replaced as explanatory constructs in psychological research and theory. To accomplish this goal, the authors (a) summarized arguments for why racial categories should be replaced; (b) used principles of the scientific method to show that racial categories lack conceptual meaning; (c) identified common errors in researchers' measurement, statistical analyses, and interpretation of racial categories as independent variables; and (d) used hierarchical regression analysis to illustrate a strategy for replacing racial categories in research designs with conceptual variables. Implications for changing the study of race in psychology are discussed.